The Effectiveness of Internal Control in Village Fund System - Audela, Kezya; Kristianti, Ika (AFRE (Accounting and Financial Review), 2022)
The Financial and Development Supervisory Agency forms Siskeudes to facilitate the village governance system and the village funds management. Internal control is one of the essential components to mitigate the risk of misuse of village funds. This study aims to analyze the implementation of internal control and the effectiveness of the implementation of internal control in controlling risk in the Siskeudes using the indicators listed in the Minister of Village Regulation Number 19 of 2015. The research was conducted in Gedangan Village using a qualitative descriptive method. The data was obtained through the process of interview and observation, analysis technique used is data triangulation. The results and discussion of the study indicate that the internal control in the village financial system has been implemented quite effectively because there are internal control efforts applied to each indicator in Minister of Village Regulation Number 19 of 2015. However, there is still a potential fraud because several internal control indicators that have been implemented not been followed up appropriately and periodically